Pemanfaatan Artificial Intelligence Sebagai Media Pembelajaran Bahasa Inggris di SDN 15 Padang Genting - Muhammad Amin; Hainur Rasyid; Akmal (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2026)
Abstract: The development of Artificial Intelligence (AI) technology offers substantial potential for providing interactive educational media, yet its implementation at the elementary education level is frequently impeded by educators' limited digital literacy. This situation was observed at SDN 15 Padang Genting, where English language instruction remains dominated by conventional methods with minimal utilization of adaptive digital media. Therefore, this community service program aims to enhance teachers' competencies and skills in utilizing AI technology as a medium for English language learning. The implementation adopted a Capacity Building approach comprising three structured stages: initial evaluation (pre-test), hands-on practice training, and final evaluation (post-test). The training focused on introducing text and visual generative AI, along with basic prompt engineering techniques. The results demonstrated a highly significant increase in teachers' capacity; comprehension of basic AI concepts surged from 15% to 85%, and the perceived ease of using the technology rose from 20% to 85%. Furthermore, the program successfully facilitated participants in independently producing educational media, such as interactive vocabulary flashcards and bilingual short stories. The hands-on training approach proved effective in overcoming the anxiety of non-technical teachers while accelerating their creativity in designing English learning materials that are relevant and engaging for digital-generation students. Keywords: artificial intelligence; capacity building; english language; learning media; teacher training. Abstrak: Perkembangan teknologi Artificial Intelligence (AI) menawarkan potensi besar dalam penyediaan media pendidikan yang interaktif, namun implementasinya di tingkat pendidikan dasar seringkali terhambat oleh keterbatasan literasi digital pendidik. Kondisi ini ditemukan di SDN 15 Padang Genting, di mana pembelajaran Bahasa Inggris masih didominasi oleh metode konvensional dan minimnya pemanfaatan media digital adaptif. Oleh karena itu, kegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan kompetensi dan keterampilan guru dalam memanfaatkan teknologi AI sebagai media pembelajaran Bahasa Inggris. Pelaksanaan kegiatan ini mengadopsi pendekatan Capacity Building yang mencakup tiga tahapan terstruktur: evaluasi awal (pre-test), pelatihan berbasis praktik langsung (hands-on practice), dan evaluasi akhir (post-test). Pelatihan difokuskan pada pengenalan AI generatif teks dan visual serta teknik rekayasa prompt dasar. Hasil kegiatan menunjukkan peningkatan kapasitas guru yang sangat signifikan; pemahaman konsep dasar AI melonjak dari 15% menjadi 85%, dan persepsi terhadap kemudahan penggunaan teknologi meningkat dari 20% menjadi 85%. Lebih lanjut, kegiatan ini berhasil memfasilitasi peserta untuk memproduksi luaran media pembelajaran secara mandiri, seperti flashcard vocabulary interaktif dan naskah cerita dwibahasa. Pendekatan pelatihan berbasis praktik terbukti efektif meruntuhkan kecemasan guru non-teknis, sekaligus mengakselerasi kreativitas mereka dalam merancang materi Bahasa Inggris yang relevan dan menarik bagi siswa generasi digital. Kata kunci: artificial intelligence; capacity building; media pembelajaran; bahasa inggris; pelatihan guru